Cleared to land? A nationwide analysis of emergency care hospital and HEMS infrastructure in Germany - Justus Wolff; Christian Hohenstein; Christian Karagiannidis; Julius Kerkhoff; Hans Morten Lossius; Johannes Strobel; Jakob Ule; Janosch Dahmen (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Healthcare systems are increasingly shifting toward specialization and centralization. As a result, distances are growing between emergency patients and suitable emergency hospitals, as well as in between hospitals for interhospital transfers. Helicopter Emergency Medical Services (HEMS) are essential in maintaining equitable access to emergency care, particularly in rural regions. However, the availability and quality of HEMS landing infrastructure at hospitals remains largely unexamined. This study provides the first nationwide integrated mapping and analysis of emergency care hospital and HEMS landing facility distribution. Methods We conducted a nationwide cross-sectional analysis of all German hospitals classified under the Emergency Care Level system (ECL I–III). Using data from hospital quality reports, government registries, and satellite imagery, we assessed the availability and type of HEMS landing facilities, categorized as certified helipads or Public Interest Sites (PIS). The study aimed to map and characterize the emergency care hospital and HEMS infrastructure, identify associated hospital and regional factors, and assess spatial access and data completeness through targeted analyses. Results Of 1,037 emergency care hospitals, 69.6% have a designated landing facility, with 44.0% of these featuring a certified helipad and 56.0% relying on PIS. A substantial proportion of hospitals (30.4%) lack any HEMS landing facility, especially in urban areas. Certified helipads are more prevalent at higher-tier emergency hospitals (ECL II and III) but no landing facility is available at 18.3% of these facilities, particularly in metropolitan regions. Hospitals in rural areas are more likely to have a HEMS landing facility. Conclusions Despite the crucial role of HEMS in emergency medical care, nearly one-third of Germany’s emergency care hospitals lack designated landing facilities, with PIS still outnumbering certified helipads. This reflects structural and regulatory shortcomings that may compromise timely access to specialized care. Enhancing national oversight, modernizing infrastructure, and adopting harmonized European standards are key measures to ensure reliable aeromedical access – and to improve patient outcomes across borders.